2017
DOI: 10.1186/s12884-017-1355-z
|View full text |Cite
|
Sign up to set email alerts
|

Lower mortality is observed among low birth weight young infants who have received home-based care by female community health volunteers in rural Nepal

Abstract: BackgroundThere has been little success in attempts to reduce the proportion of births with low birth weight (LBW). However, deaths associated with LBW may be prevented with extra attention to warmth, feeding, and prevention or early treatment of infections. There are few studies on this in Nepal and in many other developing countries. This is a cohort study to evaluate the risk of deaths among LBW infants who received FCHV follow up visit for home-based care compared to those who did not receive in Rural Nepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…The same study also identified the improved odds of mothers having better knowledge and behaviors related to MNCH after the intervention [21]. Another cohort study found that those who received follow-up visits by FCHVs had 84% less relative risk of infant deaths due to low birth weight compared to those who had no FCHVs' involvement [19]. Despite the FCHVs' role in improving MNCH indicators in the country, their specific role in promoting PPFP was unclear.…”
Section: Role Of Fchv In Community Linkagementioning
confidence: 99%
See 1 more Smart Citation
“…The same study also identified the improved odds of mothers having better knowledge and behaviors related to MNCH after the intervention [21]. Another cohort study found that those who received follow-up visits by FCHVs had 84% less relative risk of infant deaths due to low birth weight compared to those who had no FCHVs' involvement [19]. Despite the FCHVs' role in improving MNCH indicators in the country, their specific role in promoting PPFP was unclear.…”
Section: Role Of Fchv In Community Linkagementioning
confidence: 99%
“…The involvement of FCHVs in community health interventions in Nepal has effectively improved population-based coverage for various health services [17][18][19][20][21]. A post disaster health promotion intervention study involving FCHVs in an earthquake affected district in Nepal showed that their involvement helped in improving the facility delivery among the mothers from 63 to 83% [21].…”
Section: Role Of Fchv In Community Linkagementioning
confidence: 99%
“…The sharp decline in child mortality in Nepal after the 1980s has been attributed to different inexpensive community-based interventions [7,[15][16][17] led by local health workers and FCHVs. Studies around the world have shown that community-based interventions with minimal training to community health volunteers and ensuring the availability of life-saving key commodities contributes to the decline in child mortality [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…year within the first 28 days of their life in Brazil, with most deaths occurring in the first seven days after birth. Previous studies suggest that one of the most effective ways to prevent such deaths are home visiting programs, which support mothers in the first weeks of infant's lives, promote breastfeeding and kangaroo mother care, and ensure appropriate medical care when needed [2][3][4][5][6].…”
mentioning
confidence: 99%